How to listen to and appreciate jazz - Buehrer, Theodore Edward; Martin, Henry; Waters, Keith (Prince Frederick, Md. : Recorded Books, 2006)
A series of lectures designed to help musical enthusiasts become more astute, sophisticated jazz listeners. In these lectures, Professor Buehrer introduces concepts common to nearly all forms of music before focusing on unique aspects of jazz appreciation from early jazz to swing, bebop, fusion, and the contemporary jazz scene.
In container (25 cm.).
Compact discs.
Includes 2 disc music set, Jazz: the first 100 years by Henry Martin and Keith Waters (Sony, A2 93753, p2005).
Keywords: Music appreciation; Musical analysis; Jazz -- History and criticism